2006
DOI: 10.1097/qco.0b013e3280106854
|View full text |Cite
|
Sign up to set email alerts
|

Preemptive antifungal therapy: still a way to go

Abstract: The review will consider these recent developments with the purpose of introducing the concept of preemptive antifungal therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 42 publications
1
19
0
Order By: Relevance
“…Several studies have also indicated lower GM levels in patients undergoing antifungal treatment, which is an important issue in view of the increasing number of patients who receive antifungal prophylactic or preemptive treatment (9,11). Our findings with IPA patients who were treated with caspofungin indicate a potential interaction of echinocandins with the GM and the BG test results.…”
Section: Discussionsupporting
confidence: 47%
“…Several studies have also indicated lower GM levels in patients undergoing antifungal treatment, which is an important issue in view of the increasing number of patients who receive antifungal prophylactic or preemptive treatment (9,11). Our findings with IPA patients who were treated with caspofungin indicate a potential interaction of echinocandins with the GM and the BG test results.…”
Section: Discussionsupporting
confidence: 47%
“…Also, a highly suggestive CT-scan (eg, halo sign during neutropenia) and consecutive negative GM/β-D-glucan detection should trigger an aggressive diagnostic exploration for infection caused by Zygomycetes (Fig. 1) [38,39].…”
Section: Preemptive Antifungal Therapy In Hematology: the Jury Is Stimentioning
confidence: 99%
“…Conversely, a positive test would trigger an aggressive search of IA, and treatment would be instituted at an early stage of disease [22,26]. It is imperative to better identify the patient at high risk for IA and the periods of high risk, which would improve the predictive value of diagnostic testing and potentially limit overtreatment with antifungal therapy.…”
Section: Preemptive Targeted Therapymentioning
confidence: 99%